The Effect Of Stator Excitation Current On The Driving Torque Of A Single-Phase “6/6” Switched Reluctance Generator Design With External Excitation - Simatupang, Gidion; Siagian, Parlin; Dalimunthe, Muhammad Erpandi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Switched Reluctance Generators (SRGs) have attracted attention due to their robust construction, low cost, and high fault tolerance, suitable for extreme environments. However, SRGs suffer from torque ripple and acoustic noise due to the non-linear torque-excitation current relationship. Although SRG component optimization has been investigated, a gap exists in the analysis of the effect of stator excitation current on the drive torque in a single-phase